UPAYA MENINGKATKAN AKTIVITAS DAN PRESTASI BELAJAR IPA DENGAN MENGGUNAKAN METODE DEMONSTRASI PADA SISWA KELAS VI SD NEGERI 6 SIDEAK - Sitanggang, Ronny (Jurnal Tematik, 2022)
The use of the demonstration method is expected to increase student activity in the teaching and learning process so that in the teaching and learning process teaching and learning activities do not occur saturation, thus students will be physically, emotionally and intellectually involved which in turn is expected to change the concept of objects taught by the teacher can be understood by the teacher. Students The problems to be studied in this research are: (a) How is the improvement of science learning achievement by applying the demonstration method? (b) How is the effect of the demonstration method on student learning activities? While the objectives of this research are: (a) Want to know the increase in student achievement after the implementation of the demonstration method. (b) Want to know the effect of student learning activities after the demonstration method is applied. This research uses three cycles of action research. Each round consists of four stages, namely: design, activities and observations, reflection, and revision. The target of this research is Class VI students of SDN 6 Sideak, Palipi District, Samosir Regency for the 2020/2021 Academic Year. The data obtained in the form of formative test results, observation sheets of teaching and learning activities. From the results of the analysis, it was found that student learning achievement increased from cycle I to cycle III, namely, cycle I (66.67%), cycle II (76.19%), cycle III (90.00%). The conclusion of this study is that learning with the demonstration method can have a positive effect on student achievement and learning activities at SD Negeri 6 Sideak, Palipi District, Samosir Regency and this learning model can be used as an alternative learning Natural Sciences